Symmetric and Asymmetric Based Encryption Model for Mobile Commerce - Abikoye, O. C.; Dokoro, A. H.; Abdullahi, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Secure information exchange in a mobile commerce environment has become a difficult task due to the involvement of sensitive financial information and the tremendous development in information technology in recent years. This poses a great threat while conducting transaction in a mobile commerce environment. Cryptography has been employed to eliminate this using symmetric and asymmetric cryptography. However, in symmetric cryptography, secret key distribution can create a performance bottleneck, while asymmetric ciphers consume significant computational resources. This paper proposed symmetric and asymmetric based encryption model so as to achieve robust security and faster processing speed, by employing Advanced Encryption Standard (AES) as symmetric algorithm and Rivest-Shamir-Adleman (RSA) as asymmetric algorithm. In this model, RSA was used to encrypt AES secret key in order to secure the exchange of the key, while the rest of the sensitive data was encrypted using AES. The proposed model was implemented using Java programming language. Performance evaluation of the proposed model was carried out in terms of encryption/decryption time and the results show that the proposed model takes a little longer time than the RSA algorithm. This is as a result of the AES key encryption being introduced into the model. It is therefore recommended that the model be implemented in mobile commerce applications as an added layer of security in order to strengthen the applications against numerous security threats due to the robust security and faster processing speed provided by the proposed model.